Pengaruh Green Marketing Product Lele Wakoel Sidoarjo Terhadap Keputusan Pembelian - Rizal Yulianto, Mochamad; Nindia Intan Agustin; Asat Rizal (Lembaga Pengembangan Kinerja Dosen, 2022)
This study aims to determine and analyze the effect of Green Marketing Wakoel Sidoarjo catfish products on purchasting decisions partially and simultaneously to determine which variables have a significant effect.This reseaech is a descriptive study using quantitative motheodes methodes, while the population and sampel are sampele are taken by accidental samplin, where the numer of samples is 100 respondents calculated using the Lemeslow formula. Data collection techniques using qustionnaires that are measured using a Likert scale. The results of this study indicate that study indicate that partially green product, green price, green place, green promotion has a positive and significant effect on purchassing decisions of Wakoel Sidoarjo products with a value a value >, which is above 1,660. The result of simultaneous test, it is known that green product, green price, green plice, green promotion simultaneously influence the purchasing decision of the Wakoel Sidoarjo product w with a value of 15.630. while the results of beta or significanece tests show that the green product hypothesis is proven to be the most significant indepent variabel on purchasing decisions with a 0.529 so that it is concluded that green products have a strong enough influence on purchasing de disions.